2017
DOI: 10.1080/00275514.2017.1410422
|View full text |Cite
|
Sign up to set email alerts
|

Two newGeosmithiaspecies inG. pallidaspecies complex from bark beetles in eastern USA

Abstract: Species of Geosmithia are cosmopolitan but understudied fungi, and most are associated with phloem-feeding bark beetles on various woody hosts. We surveyed 207 bark and ambrosia beetles from 37 species in the eastern USA for associated fungi. The community is dominated by species in the G. pallida species complex (GPSC) and included several Geosmithia isolates that appear to be new to science. The new Geosmithia isolates exhibited the characteristic brownish-colored colonies typical for the G. pallida species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 41 publications
1
26
1
Order By: Relevance
“…where adults do not enter these tissues. Although, there are many studies confirming associations between ambrosia beetles and Geosmithia fungi [8,10,11,14,16], our study showed that T. lineatum does not transmit Geosmithia. There was also no evidence that this ambrosia beetle can transmit Geosmithia fungi in pine habitats [9].…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…where adults do not enter these tissues. Although, there are many studies confirming associations between ambrosia beetles and Geosmithia fungi [8,10,11,14,16], our study showed that T. lineatum does not transmit Geosmithia. There was also no evidence that this ambrosia beetle can transmit Geosmithia fungi in pine habitats [9].…”
Section: Discussioncontrasting
confidence: 67%
“…There was also no evidence that this ambrosia beetle can transmit Geosmithia fungi in pine habitats [9]. The genus Geosmithia currently includes 44 recognized taxa with only 16 described to date, most of which are associated with phloem-breeding bark beetles [4,5,[7][8][9][10][11][12][13][14][15][16]. In the present study, we identified two distinct Geosmithia operational taxonomic units (OTUs) based on morphological and molecular characterizations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…3 and Geosmithia sp. 23 which are know from various bark beetle hosts in Europa, USA and Seychelles (Kolařík et al 2007(Kolařík et al , 2008(Kolařík et al , 2017Huang et al 2017Huang et al , 2019, and further study need to clarify among these three lineages. In this study, we isolated G. pulverea from A. gracilipes, Gne.…”
Section: Discussionmentioning
confidence: 99%
“…It was consequently recognized, using multigene phylogeny, together with Geosmithia sp. 23, as a well-de ned phylogenetic species inside the G. pallida species complex (Kolařík et al 2017;Huang et al 2017). The colony of G. pulverea was very similar to Geosmithia sp.…”
Section: Distributionmentioning
confidence: 99%